(untitled) (College of Basic Education Research Journal, 2026)
dministrative organizations, in general, possess unique characteristics that distinguish them from others. This is naturally due to the differences in intellectual and cultural patterns that govern organizational behavior. Consequently, each organization has a distinct personality, and this distinctiveness, as an administrative concept, is called the organization’s culture. The current research aims to identify the level of organizational culture among representatives of the Olympic Committee in Nineveh Governorate from the perspective of members of the sub-federations. The researchers used the descriptive survey method, as it is suitable for the nature of this research. The research population consisted of (85) members of the Olympic sub-federations. The research sample comprised (77) members of the sub-federations who fully completed the research scale, leaving no item unanswered. The Organizational Culture Scale by Alian (2012) was used, and the researchers employed the SPSS statistical package and the percentage formula. The researchers reached the following conclusions: 1- The level of organizational culture among the representatives of the Olympic Committee in Nineveh Governorate was identified from the perspective of the members of the sub-federations. 2- The representatives of the Olympic Committee in Nineveh Governorate possess a high (very good) level of organizational culture from the perspective of the members of the sub-federations. The researchers recommend the following: 1- Implementing the scale used in this research by the representatives of the Olympic Committee as a benchmark for continuous development and improvement. 2- Emphasizing such research and studies and involving representatives of the Olympic Committee in seminars, courses, and conferences that support creativity and contribute to raising and developing their organizational culture.